Infused water Zaman Nabi Saw untuk Perilaku Sehat di Masa Covid-19: Studi Takhrij dan Syarah Hadits - Nami Naluri Nupasti; Muhamad Yoga Firdaus; Cucu Setiawan (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to analyze the hadith about infused water during the prophet's time for healthy behavior during the covid-19 era. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods with contemporary analysis. The results of the research and discussion show that the hadith about infused water during the prophet's time for healthy behavior during the Covid-19 period is of authentic quality based on a review of the takhrij hadith because there are no syadz (odd) and 'illat (disabled), so that it can be practiced and used as an argument. The explanation of this hadith shows that infused water is not just ordinary soaking water, it is not only delicious to eat but also an easy and cheap recipe and also refers to the Koran and Sunnah, because infused water is the favorite drink of the Prophet which has many One of the benefits for healthy behavior during this Covid-19 period is maintaining immunity.